Provision of powered communication aids in the United Kingdom. (3rd July 2017) - Judge, Simon; Enderby, Pam; Creer, Sarah; John, Alex
Abstract: AAC service provision in the United Kingdom (UK) has evolved since the first service dedicated to the provision of communication aids opened in 1986. Within the UK, many health and care services are provided via government funding; however, the assessment and provision of AAC and specifically of speech-generating devices (SGDs) is inconsistent and inequitable. The study reported in this paper aimed to collect information on levels of current provision of powered communication aids (the term used in the study to refer to SGDs) by UK service providers in 2013 with the intention of improving future estimates for need of services. A questionnaire survey was designed and data were obtained from 98 AAC services across the UK. Service providers reported the number of individuals known to be using powered communication aids and the mean value reported was 0.0155% of the services' catchment populations. However levels of service provision reported were highly variable. Although the data reported must be treated with caution, it adds to the sparse literature on the topic, informs AAC service design and delivery in the UK, and acts as an indicative baseline measure for future service development.